2018
DOI: 10.1016/j.placenta.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary metabolomics analysis of placenta in maternal obesity

Abstract: Placental metabolome analysis of obese pregnancies showed differences in metabolites involved in antioxidant defenses, nucleotide production, as well as lipid synthesis and energy production, supporting a shift towards higher placental metabolism. OB placentas also showed a specific fatty acids profile suggesting a disruption of LC-PUFA biomagnification. This study can lay the foundation to further metabolomic placental characterization in maternal obesity. Metabolic signatures in obese placentas may reflect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 46 publications
0
62
0
Order By: Relevance
“…Recently, the placental metabolome has become a topic of great interest as changes in the relative concentrations of metabolites occur in some complicated pregnancies (Fattuoni et al, 2018). We analyzed fifty-one polar/ionic metabolites in placental extracts normalized to dried tissue weight using multisegment injection-capillary electrophoresis-mass spectrometry (MSI-CE-MS).…”
Section: Maternal Hfd Alters Placental Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the placental metabolome has become a topic of great interest as changes in the relative concentrations of metabolites occur in some complicated pregnancies (Fattuoni et al, 2018). We analyzed fifty-one polar/ionic metabolites in placental extracts normalized to dried tissue weight using multisegment injection-capillary electrophoresis-mass spectrometry (MSI-CE-MS).…”
Section: Maternal Hfd Alters Placental Metabolomicsmentioning
confidence: 99%
“…Recently, the placental metabolome has become a topic of great interest as changes in the relative concentrations of metabolites occur in some complicated pregnancies (Fattuoni et al, 2018). We analyzed fifty-one polar/ionic metabolites in placental extracts normalized to dried tissue weight using multisegment injection-capillary electrophoresis-mass log-transformed, autoscaled, dried mass normalized R 2 = 0.748, Q 2 = 0.598 The dashed box within VIP plot highlights that 6 placental metabolites were found to be significantly lower in high-fat placentas when using a FDR adjustment (q < 0.05).…”
Section: Maternal High-fat Diet Alters Placental Metabolomicsmentioning
confidence: 99%
“…Through GC-MS, significant differences in antioxidant metabolites, nucleotide production, lipid synthesis and energy production were detected. In detail, obese mothers' placentas also showed a peculiar fatty acids profile, related to an increase in placental metabolism and potentially reflecting intrauterine changes responsible of later diseases, including metabolic syndrome and cardiovascular disease [33].…”
Section: Metabolomics In Obstetricsmentioning
confidence: 98%
“…Moreover, recent evidence highlights the pivotal role played by the placenta during fetal life. Such structure can be defined a metabolic interface between the mother and the fetus, influencing neonatal maturation and metabolism [33].…”
Section: Metabolomics In Obstetricsmentioning
confidence: 99%
“…39 Investigators using metabolomics have shown that obesity causes profound changes in pregnant women that are distinguishable in a variety of body fluids and tissue samples and suggest multiple ways in which obesity changes metabolism. 40,41 For this reason, we examined the withingroup influence of maternal delivery BMI by creating obese and nonobese groups (BMI at hospital admission < or ! 30 kg/m 2 ) of cases and controls for metabolomics analyses.…”
Section: Study Participantsmentioning
confidence: 99%